Characterization of two novel bacteriophages (PSV6 and PSV3) as biocontrol agents against Pseudomonas syringae - Zhang, Shengting; Zhao, Sha; Li, Jinhua; Zou, He; Ju, Yani; Xiang, Yangjian; Wei, Yunlin (Frontiers in Microbiology, 2025)
Pseudomonas syringae is a prevalent plant-pathogenic bacterium. Conventional control strategies, such as fungicides, copper-based compounds, and antibiotics, often result in elevated environmental toxicity and promote the emergence of bacterial resistance. Consequently, bacteriophage-based biocontrol has garnered considerable attention as an eco-friendly alternative. In this study, two novel bacteriophages, PSV6 and PSV3, were isolated from wastewater using Pseudomonas syringae pv. syringae (Pss) as the host strain. Transmission electron microscopy and whole-genome phylogenetic analyses indicated that both phages belong to the class Caudoviricetes, with PSV6 classified within Autotranscriptaviridae and PSV3 within Jondennisvirinae. The one-step growth characteristics, as well as the thermal, pH, and solvent stabilities of PSV6 and PSV3, were further evaluated under different solvent conditions. Their host range, a critical factor for their environmental applications, was also assessed. Whole-genome sequencing revealed that the genome of PSV6 is 40,070 bp in length and contains 48 open reading frames (ORFs), whereas that of PSV3 is 229,871 bp long and comprises 376 ORFs, with no virulence factors or antibiotic resistance genes detected. In vivo assays in Arabidopsis thaliana demonstrated that increasing phage titers enhanced biocontrol efficacy against Pss. Notably, treatment with both phages was more effective than treatment with PSV6 alone. Moreover, treatment with PSV3 at a multiplicity of infection of 100 exhibited the strongest preventive and therapeutic effects against Pss. Overall, our results highlight the potential of PSV6 and PSV3 as sustainable alternatives to chemical pesticides in agriculture.